Outcome of pulmonary sarcoidosis: a population-based study 1976-2013 - Ungprasert, Patompong; Crowson, Cytnthia S; Carmona, Eva M; Matteson, Eric L (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: A hallmark of sarcoidosis is lung disease. However, the prognosis and long-term outcome of pulmonary sarcoidosis are not well-defined due to the limited number of studies with long duration of follow-up. Objectives: This study was undertaken to characterize the course of pulmonary sarcoidosis in a population-based cohort. Methods: A population-based cohort of 311 incident cases of pulmonary sarcoidosis among Olmsted County, Minnesota residents in 1976-2013 were identified. Medical records of the confirmed cases were reviewed from diagnosis to last follow-up. Data on stage of pulmonary sarcoidosis at diagnosis, serial pulmonary function tests, requirement of oxygen therapy and treatment were abstracted. The cumulative incidence of chronic respiratory impairment (defined as forced vital capacity of <50%, diffuse capacity for carbon monoxide of <40% or requirement to use oxygen supplementation) adjusted for the competing risk of death was estimated. Cox models were used to assess the association of stage of pulmonary sarcoidosis and treatment on the development of chronic respiratory impairment. Results: 25 patients developed chronic respiratory impairment which corresponded to a 10-year event rate of 4.4% (95% confidence interval [CI], 1.9.-6.9). Stage of pulmonary sarcoidosis at diagnosis was a strong predictor for chronic respiratory impairment with hazard ratio compared with stage I of 5.29 (95% CI, 1.65-16.96) for stage II and 8.36 (95% CI, 26.3-26.52) for stage III and IV. Use of glucocorticoids and immunosuppressive agents was associated with a significantly increased risk of chronic respiratory impairment. Conclusion: Patients with pulmonary sarcoidosis have a good pulmonary prognosis with a low incidence of chronic respiratory impairment.